Increasing supporting rod porcelain isolate at electric power substations. Issue 5 (April 2020) - Lukovenko, A S; Kukartsev, V V; Tynchenko, V S; Bashmur, K A; Kukartsev, V A; Cherepanov, A I
Abstract: Supporting rod insulation is intended for insulating and fastening cathode parts of electrical installations at electric power substations. The insulation is set at outdoor switchgear of substations as a part of the main switchgear equipment. During the operation, it is exposed to external atmospheric influences, mechanic and dynamic loads. Timely replacing supporting rod insulation significantly increases the reliability of the main substation equipment at electric power substations. There was considering a question about improving the reliability at transformer and traction substations, providing internal and external conditions affected the destruction of supporting rod porcelain insulation. It was determined that an important negative part of supporting rod porcelain insulation damage is sharp swings of ambient temperature, especially swinging values after 0 ºC. A model is suggested for applying a supporting rod porcelain insulator as an insulating body in the ellipse form. It was described the suggested device work. The temperature gradient was taken into account, which shows the intensity of the temperature changing, is a vector directed towards the increasing temperature. There is an equation of a temperature field, which describes a thermal state of the body and determines a degree of its heating. There is an analyzing interacting ratio of values of circle axis and oval from larger to smaller in the spatial positioning in power loads, comparing a section form. The calculation determined a post insulator in the ellipse form should be set in the way where the long axis will be compatible in the gradient direction of temperature for decreasing influences of heating to the minimal axis of the insulator.